Development of a method for on-board measurement of instant engine torque and fuel consumption rate based on direct signal measurement and RGF modelling under vehicle transient operating conditions. (15th December 2019) - Li, Yangyang; Duan, Xiongbo; Fu, Jianqin; Liu, Jingping; Wang, Shuqian; Dong, Hao; Xie, Yunkun
Abstract: In this paper, a hybrid approach of coupling signal measurement as well as parameters modelling is proposed to indirectly measure engine torque and fuel consumption rate under transient operating conditions. The RGF model is simplified from the complex three dynamic pressure (3DP) transducers method and changed into a two steady pressure (2SP) sensors method, which makes it readily applicable for vehicle on board applications. Compared to actual measurement from the torque and fuel flow meters, the results showed that the method developed in this paper achieved reasonable accuracy. In terms of RGF, the relative errors between the measured and simulated results are within 5% both at steady-state and transient operating conditions. In terms of measured and simulated instant torque, the relative errors are within 5% both at steady-state and transient operating conditions and the absolute errors are ± 5N.m on the NEDC cycle. In addition, in terms of measured and simulated fuel consumption rate, the relative errors of cumulative consumption fuel are within 3% in the NEDC cycle. This method could be applied to reveal, analyze and optimize the detailed process of an automotive engine under transient operating conditions. Highlights: A simplified RGF model is developed based on 2SP sensors method. On-line measure engine torque model is developed according to the RGF model. On-line fuel consumption is developed based on developed RGF model.